Acupuncture for Opioid Dependence Patients Receiving Methadone Maintenance Treatment: A Network Meta-Analysis - Wen, Hao; Chen, Rouhao; Zhang, Peiming; Wei, Xiaojing; Dong, Yu; Ge, Shuqi; Luo, Wen; Zhou, Yiping; Xiao, Songhua; Lu, Liming (Frontiers in Psychiatry, 2021)
Background: Opioid dependence has been a threat to public health for over hundreds of years. With the increasing number of studies on acupuncture-related therapies for opioid dependence patients receiving methadone maintenance treatment (MMT), its effect of acupuncture therapy in treating MMT patients remains controversial. Therefore, we conducted a multiple-treatments meta-analysis, and incorporated both direct and indirect comparisons, in order to discover the most effective treatment for opioid dependence patients receiving MMT. Methods: Three English databases and three Chinese databases were searched from its inception to August 20, 2020, in order to compare the effects of acupuncture-related therapies and MMT, which was summarized as western medicine (WM) in the following texts. A pair-wise meta-analysis was conducted using the RevMan software (Version 5.3), the quality of studies was assessed according to Cochrane’s risk of bias tool 5.1.0, and a network meta-analysis was performed using the R software (Version 3.6.1) and STATA (Version 14.0). The primary outcome was the effective rate, which was calculated by the ratio of detoxifying patients to the total. The secondary outcome was the Modified Himmelsbach Opiate Withdrawal Scale (MHOWS). Results: A total of 20 trials were included, which consisted of comparisons among WM, traditional Chinese medicine (TCM), and the four types of acupuncture, namely, manual acupuncture (MA), electro-acupuncture (EA), auricular acupuncture (AA), and transcutaneous electrical acupoint stimulation (TEAS). Though none of the trials were at low risk of bias. In the pair-wise meta-analysis, no statistically significant differences were observed in terms of the effective rate. Furthermore, MA was more efficacious than WM, EA and TEAS in MHOWS, with mean differences (MDs) of (-8.01, 95%CI: -11.93 to -4.09, P<0.00001), (-6.15, 95%CI: -9.45 to -2.85, P=0.0003), and (-10.44, 95%CI: -16.11 to -4.77, P=0.0003), respectively. In the network meta-analysis, MA was more effective than WM (RR:1.40, 95% CI: 1.05 to 1.99) on the effective rate, and (MD: -5.74, 95% CI: -11.60 to -0.10) on MHOWS. TEAS was more effective than WM (MD: -15.34, 95% CI: -27.34 to -3.46) on MHOWS. Synthetically, MA had the highest probability to rank first in treating opioid dependence.